Engineering the Oryza sativa cell wall with rice NAC transcription factors regulating secondary wall formation - Yoshida, Kouki; Sakamoto, Shingo; Kawai, Tetsushi; Kobayashi, Yoshinori; Sato, Kazuhito; Ichinose, Yasunori; Yaoi, Katsuro; Akiyoshi-Endo, Miho; Sato, Hiroko; Takamizo, Tadashi; Ohme-Takagi, Masaru; Mitsuda, Nobutaka (Frontiers in Plant Science, 2013)
Plant tissues that require structural rigidity synthesize a thick, strong secondary cell wall of lignin, cellulose and hemicelluloses in a complicated bridged structure. Master regulators of secondary wall synthesis were identified in dicots, and orthologs of these regulators have been identified in monocots, but regulation of secondary cell wall formation in monocots has not been extensively studied. Here we demonstrate that the rice transcription factors SECONDARY WALL NAC DOMAIN PROTEINs (SWNs) can regulate secondary wall formation in rice (Oryza sativa) and are potentially useful for engineering the monocot cell wall. The OsSWN1 promoter is highly active in sclerenchymatous cells of the leaf blade and less active in xylem cells. By contrast, the OsSWN2 promoter is highly active in xylem cells and less active in sclerenchymatous cells. OsSWN2 splicing variants encode two proteins; the shorter protein (OsSWN2S) has very low transcriptional activation ability, but the longer protein (OsSWN2L) and OsSWN1 have strong transcriptional activation ability. In rice, expression of an OsSWN2S chimeric repressor, driven by the OsSWN2 promoter, resulted in stunted growth and para-wilting (leaf rolling and browning under normal water conditions) due to impaired vascular vessels. The same OsSWN2S chimeric repressor, driven by the OsSWN1 promoter, caused a reduction of cell wall thickening in sclerenchymatous cells, a drooping leaf phenotype, reduced lignin and xylose contents and increased digestibility as forage. These data suggest that OsSWNs regulate secondary wall formation in rice and manipulation of OsSWNs may enable improvements in monocotyledonous crops for forage or biofuel applications.